Using JMP 13 (SAS Institute, 2016)
Using JMP 13 shows you how to perform common tasks such as importing data, setting column properties, exporting analyses as graphics or HTML, and modifying JMP preferences. Details about connecting to SAS and working in the Formula Editor are also provided.
Includes index. - Online resource; title from title page (viewed September 22, 2016)
Keywords: JMP (Computer file); Statistics -- Graphic methods; Mathematical statistics -- Data processing; Information visualization; Mathematical analysis; Statistique; Méthodes graphiques; Statistique mathématique; Informatique; Visualisation de l'information; Analyse mathématique; COMPUTERS; Data Processing; Mathematical statistics; Data processing; Statistics; Graphic methods